ANALISIS KESULITAN SISWA MADRASAH TSANAWIYAH DALAM MENYELESAIKAN SOAL LINGKARAN - Anas Muharrom; Gida Kadarisma (IKIP Siliwangi, 2022)
The objectives of the study was to analyze students difficulties in circle material questions. Descriptive qualitative method is used in this study to describe the students difficulties. 20 students of IX E class in MTs Al-mukhtariyah mande are the subject of this study. Data collection technique used test. In Addition, data analysis using three main components : data reduction, data display and verifying conclusion. The result of this study show that that the indicator of the common tangent of two circles is the highest error (80%) and determine relationship between angle at centre and angle at circumference question indicator is the lowest error (33%). Several factors cause students difficulties, there are (1) difficulty in comprehending the concept of a circle, (2) difficulty in applying appropriate formula, (3) difficulty in operate math questions, and (4) difficulty in accurately answer the question.